Sensory impairments, problems of balance and accidental injury at work: a case–control study. Issue 3 (18th December 2014) - Palmer, Keith T; D'Angelo, Stefania; Harris, E Clare; Linaker, Cathy; Coggon, David
Abstract : Objectives: Sensory impairments are becoming increasingly common in the workforces of Western countries. To assess their role in occupational injury, and that of disorders of balance, we undertook a case–control study. Methods: Using the Clinical Practice Research Datalink, which documents all medical consultations, referrals and diagnoses in primary care for 6% of the British population, we identified 1348 working-aged patients who had consulted medical services over a 22-year period for workplace injury (cases) and 6652 age-matched, sex-matched and practice-matched controls. Risks were assessed by conditional logistic regression, for earlier recorded diagnoses of visual impairment, common eye diseases, hearing loss, perforated ear drum, non-acute otitis media and disorders of balance. Results: In all, 173 (2.2%) participants had an earlier eye problem, 792 (9.9%) an ear problem (including 336 with impaired hearing and 482 with non-acute otitis media) and 266 (3.3%) a disorder of balance. No associations were found with glaucoma, cataract, retinal disorders or perforation of the ear drum specifically, but adjusted ORs were moderately elevated for eye and ear problems more generally, and higher where there was a record of blindness or partial sight (OR 1.90, 95% CI 1.05 to 3.44) or non-acute otitis media (OR 2.04, 95% CI 1.64 to 2.54). Risks for non-acute otitis media and for disorders of balance were particularly elevated for consultations in the 12 months preceding injury consultation (OR 2.70, 95% CI 1.58 to 4.62 and 1.77, 95% CI 1.01 to 3.11, respectively). Conclusions: Problems of vision, impairments of hearing and disorders of balance all may carry moderately increased risks of occupational injury.